Fiscal Development of Area Schools. Revised - Iowa State Dept. of Public Instruction, Des Moines. Area Schools Div.; Iowa State Dept. of Public Instruction, Des Moines. Area Schools Div. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1984)
Information on the funding of the area school system in Iowa is provided. First, the report provides background information on the history and funding of the system, which was established in 1965 to meet local and state needs of adults for postsecondary and adult education. The report indicates that the funding sources available to the area schools at their inception for operational purposes have remained approximately the same, though the percentages of funds derived from these sources have varied, over a 12-year history of the system. Next, the following funds utilized by the area schools are identified and explained: current general fund, restricted current general fund, auxiliary fund, agency fund, scholarship fund, loan fund, plant funds, and endowment fund. Next, the paper reviews the funding problems experienced by the area schools since their inception, stressing the difficulties arising from inadequate funds and uncertainty about available revenues. An explanation is provided of the funding formula established in 1971 to deal with these problems, followed by a year-by-year analysis of the funding plans that have been used biennially since this time. Changes in procedures, income sources, methods of determining allocations, and supplemental aid requests are detailed. Financial data are appended. (AYC)
ERIC Note: Revised and updated version of a paper presented by Dr. Robert D. Benton at a Meeting of the Postsecondary Education Funding Committee (Des Moines, IA, July 12, 1974). This paper is included in JC 850 371.
Policymakers.
Administrators.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Community Colleges; Educational Finance; Educational History; Financial Policy; Financial Problems; Financial Support; State Aid; Two Year Colleges; Iowa; Reports, Descriptive; Numerical/Quantitative Data